Implementasi Model Pembelajaran Project Based Learning dalam Pembelajaran Matematika Tingkat Perguruan Tinggi - Masli Nurcahya Zoraida; Unan Yusmaniar Oktiawati; Al Ikhlas; Gusnidar Gusnidar; Nur Fitriani Sahamony; Joni Wilson Sitopu (Journal on Education, 2024)
Project-based learning (PjBL) is one of the student-centred learning models that can be effectively applied in mathematics learning in higher education. This study aims to analyse the implementation of PjBL in mathematics learning in higher education. The research method used is a literature study by collecting and reviewing research articles related to the implementation of PJBL in mathematics learning in higher education. The results showed that the implementation of PjBL in mathematics learning in higher education can improve students' concept understanding, problem solving ability, creativity, and learning motivation. PjBL encourages students to be actively involved in the learning process through project activities that are relevant to real life. Lecturers act as facilitators who guide students in planning, implementing and evaluating projects. Challenges in implementing PjBL include the availability of learning resources, time allocation, and project assessment. The implication of this study is the need for training for lecturers in designing and implementing PjBL effectively to achieve mathematics learning objectives in higher education.